Teori Pengetahuan dan Kebenaran dalam Epistemologi - Sherly Aulia (Undiksha, 2022)
Epistemology as a branch of philosophy determines character, knowledge and even determines which truths are considered worthy of acceptance, and which ones should be rejected. Therefore, several questions are usually asked to examine issues in epistemology, namely what isknowledge, what are the sources and basis of knowledge? Is this knowledge a definite truth or isit just conjecture? To answer all the knowledge about epistemology, this article will examine moredeeply about the theory of knowledge and truth in epistemology. The method used in writing thisarticle is a literature study. After presenting several explanations from various literary sources so that it can be said that it is almost impossible to talk about